The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/aos.13680
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in patients with retinitis pigmentosa who have normal visual acuity

Abstract: PurposeTo investigate flow area changes measured using optical coherence tomography angiography (OCTA; RTVue XR Avanti®) in patients with retinitis pigmentosa (RP) with preserved visual acuity (VA).MethodsThis was an age‐ and refraction‐matched case–control study. Consecutive patients with a best‐corrected visual acuity (BCVA) of ≥20/20 and normal subjects were recruited. Fifty eyes (32 patients) and 22 eyes (12 controls) were included. The flow area and foveal avascular zone (FAZ) were measured in both superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Inooka and colleagues described decreased perfusion density and vessel length density in the superficial and deep capillary plexus and whole retina in RP eyes compared to controls [33]. Takagi et al examined flow area in both the superficial and deep capillary plexus and similarly showed that these parameters were lower in RP eyes vs. controls [34]. Wang and colleagues examined the foveal and parafoveal subfields and found that the vessel area densities in the superficial capillary plexus in all subfields in RP eyes were lower than in control eyes [35].…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 99%
See 2 more Smart Citations
“…Inooka and colleagues described decreased perfusion density and vessel length density in the superficial and deep capillary plexus and whole retina in RP eyes compared to controls [33]. Takagi et al examined flow area in both the superficial and deep capillary plexus and similarly showed that these parameters were lower in RP eyes vs. controls [34]. Wang and colleagues examined the foveal and parafoveal subfields and found that the vessel area densities in the superficial capillary plexus in all subfields in RP eyes were lower than in control eyes [35].…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 99%
“…A qualitative study using wide angle swept source OCTA by Miyata and colleagues, with 43 RP eyes and 12 healthy eyes, demonstrated that concentric and vermicular choriocapillaris flow deficits were observed in 23% and 40% of RP eyes, respectively, and 0% of healthy eyes [38]. However, other studies showed no difference in choriocapillaris flow parameters between RP and control eyes [28,31,34]. Some authors have attributed this discrepancy to the size of OCTA images captured.…”
Section: Octa In Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…22,24,28 This limits the ability to accurately separate and quantify OCT angiograms into the three distinct macular vascular layers described in histologic studies: superficial vascular complex (SVC), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). 29 Thus, previous investigations of OCTA in RP described microvascular changes in up to 2 vascular layers; the superficial and deep capillary plexuses, [30][31][32] dividing the ICP between the superficial and deep layers. Two layer segmentation could lead to inaccurate quantification of retinal perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…31,33,34,40,42,43 In this study we found the most frequent ABCA4 mutation p.G1961E in two unrelated STGD patients, it has been reported in patients from African American and European ancestry with the frequencies of 2% and 11% respectively. 44,45 Recently, the different stages of an 'optical gap' have been described on the SD-OCT in patients with p.G1961E mutations. 46…”
Section: Family: Sg-04mentioning
confidence: 99%